2002
DOI: 10.1073/pnas.142307199
|View full text |Cite
|
Sign up to set email alerts
|

Ancestral polymorphism and adaptive evolution in the trichothecene mycotoxin gene cluster of phytopathogenic Fusarium

Abstract: Filamentous fungi within the Fusarium graminearum species complex (Fg complex) are the primary etiological agents of Fusarium head blight (scab) of wheat and barley. Scab is an economically devastating plant disease that greatly limits grain yield and quality. In addition, scabby grain is often contaminated with trichothecene mycotoxins that act as virulence factors on some hosts, and pose a serious threat to animal health and food safety. Strain-specific differences in trichothecene metabolite profiles (chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
428
1
5

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 483 publications
(456 citation statements)
references
References 27 publications
22
428
1
5
Order By: Relevance
“…In the Fg clade, phylogenetic lineages are linked to the geographic origin of isolates (O'Donnell et al 2000;O'Donnell et al 2004;Ward et al 2002), but this is not the case with F. pseudograminearum as seen in the current study. In the tree topology generated from the MLS data set, clades Fps 2 (Australia and USA), Fps 4 (New Zealand and Canada) and Fps 6 (Australia, Canada and South Africa) contained isolates from multiple regions.…”
Section: A U T H O R ' S P E R S O N a L C O P Ycontrasting
confidence: 67%
See 2 more Smart Citations
“…In the Fg clade, phylogenetic lineages are linked to the geographic origin of isolates (O'Donnell et al 2000;O'Donnell et al 2004;Ward et al 2002), but this is not the case with F. pseudograminearum as seen in the current study. In the tree topology generated from the MLS data set, clades Fps 2 (Australia and USA), Fps 4 (New Zealand and Canada) and Fps 6 (Australia, Canada and South Africa) contained isolates from multiple regions.…”
Section: A U T H O R ' S P E R S O N a L C O P Ycontrasting
confidence: 67%
“…Conversely, the former F. graminearum Group 2 has been subject to in depth study in recent times probably because of its close association with FHB worldwide. Cumulative sequencing and phylogenetic comparison of 11 nuclear genes has demonstrated that F. graminearum (hereafter referred to as the Fg clade) consists of nine distinct lineages (O'Donnell et al 2000;O'Donnell et al 2004;Ward et al 2002), each of which have been proposed for formal species status (O'Donnell et al 2004). The presence of nine phylogenetic species within the Fg clade, begs the question of whether a similar lineage development/speciation has occurred within its close relative, F. pseudograminearum.…”
Section: A U T H O R ' S P E R S O N a L C O P Ymentioning
confidence: 99%
See 1 more Smart Citation
“…Fusarium spp. express a CYP65 trichothecene C-15 hydroxylase (Tri11, 35% identity with DtxS2) involved in trichothecene biosynthesis (36). The Aspergillus parasiticus CYP65 VerB (33% identity with DtxS2) in the aflatoxin biosynthesis cluster is involved in desaturation of versicolorin B to versicolorin A (37).…”
Section: Discussionmentioning
confidence: 99%
“…Variation in trichothecene chemotypes may have important implications for toxicity (Forsell and Pestka 1985;Luongo et al 2008;Minervini et al 2004). In addition, chemotype differences have been maintained by selection and may have important consequences for pathogen fitness in different environments (Ward et al 2002). In Europe, 15-ADON is observed in South and Central European countries (Boutigny et al 2014;Jennings et al 2004;Talas et al 2011;Toth et al 2005), whereas in northwestern parts of Europe, 3-ADON has dominated (Fredlund et al 2013;Langseth et al 1999;Nielsen et al 2012;Yli-Mattila et al 2009).…”
Section: Introductionmentioning
confidence: 99%